THE ROLE OF PROFITABILITY AS AN INTERVENING VARIABLE ON THE EFFECT OF INFLATION, INTEREST RATES, AND EXCHANGE RATES ON STOCK RETURNS (STUDY ON CONSUMER GOODS INDUSTRY SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2020 PERIOD) - Emma Suryani; Yesi Mardiana (Management Science Research Journal, 2022)
Purpose: This study aims to look into and evaluate the overall effects of inflation, interest rates and currency rates on stock returns through profitability. Methodology/approach: The research firm used a purposive sample of 26, using secondary data and causality research methodologies with a quantitative approach. The population of the study consists of 41 companies. Using E-views V.11 software, the data analysis method employed is panel data analysis and path analysis. Results/Findings demonstrate that exchange rates, interest rates, and inflation negatively impact profitability. Furthermore, profitability directly has a significant positive impact on stock returns, but inflation, interest rates, and currency rates have a significant negative impact. The path analysis's findings demonstrate that profitability cannot mitigate the stock return effects of inflation, interest rates, and currency rates. Limitations: during the research period 2017-2020, using one sample from the manufacturing subsector, namely the consumer goods industry subsector. Contribution: it is expected that investors need to consider macroeconomic aspects such as inflation, interest rates, and exchange rates, which are announced every month because they will pose an investment risk. Then investors need to consider profitability because high profitability will increase stock prices and provide investors with profits. Novelty: inconsistencies in previous studies made the authors add profitability as a mediating factor and data processing using panel data on the consumer goods industry subsector in this study.